Oral health of elite athletes and impact on performance - Gallagher, J. (UCL Eastman Dental Institute, 2020)
Oral health is integralto general health, wellbeing and quality of life. Based upon the hypothesis that oral health might affect sport performance, the aim of this PhD was to investigate the association between oral health of elite athletes and self-reported performance impacts. Three studies were conducted: 1) a systematic review of self-reported outcome measures used to evaluate the impact of injury and illnesson performance in sport, 2) a cross-sectional clinical and questionnaire-based study to investigate oral health andassociated self-reported impacts, self-reported oral health behaviours, risks to oral health and opportunities for behaviour change in a representative sample of elite athletes 3) a repeated-measures study to determine the effectiveness of simple interventions, based on contemporary behaviour change theory, to improve oral health and reduce performance impacts in an opportunistic sample of elite athletes. Study 1 identified that the Oslo Trauma Research Centre (OSTRC) overuse injury questionnaire could be modified to measure the impact of oral health problems on performance in sport. The results from Study 2 confirmed that dental caries, erosion and periodontal diseases are commonin elite athletes. Although severe impacts on performance in sport were infrequent, athletes reported psychosocial impacts more frequently. Athletes said they were willing to consider adopting enhanced oral hygiene behaviours to mitigate the risks to oral health from participation in sport. Study 3 demonstrated effectiveness through improvements in athlete knowledge, self-reported oral hygiene behaviours and performance impacts. This PhD thesis provides evidence of potential negative effects on performance in sport from oral health problems based on self-reported impacts. It also demonstrates that preventive interventions, based on contemporary behaviour change theory, appeared to have some success and thereforemay reduce performance impacts in elite sport. A new model is proposed to guide effective implementation of interventions